Indonesian Traditional Medicines: The Use Before And During The COVID-19 Pandemic At Online Pharmacy Networks In Indonesia - Happy Elda Murdiana; Mega Karina Putri; Dewi Rahmawati; Aloysia Yossy Kurniawati (Poltekkes Kemenkes Surakarta, 2022)
Background: Many countries' use of traditional medicine during the COVID-19 pandemic aims to increase immunity and reduce symptoms caused by COVID-19. The use of traditional medicine, either alone or in combination with